2016
DOI: 10.1371/journal.pone.0154236
|View full text |Cite
|
Sign up to set email alerts
|

Investigating Cooperative Behavior in Ecological Settings: An EEG Hyperscanning Study

Abstract: The coordinated interactions between individuals are fundamental for the success of the activities in some professional categories. We reported on brain-to-brain cooperative interactions between civil pilots during a simulated flight. We demonstrated for the first time how the combination of neuroelectrical hyperscanning and intersubject connectivity could provide indicators sensitive to the humans’ degree of synchronization under a highly demanding task performed in an ecological environment. Our results show… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
135
0
5

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 159 publications
(152 citation statements)
references
References 64 publications
2
135
0
5
Order By: Relevance
“…More recently, Shou et al (2012) found that “the frontal theta EEG activity was a sensitive and reliable metric to assess workload […] during an ATC task at the resolution of minute (s).” The same findings have been highlighted by Borghini et al (2013) involving pilots in flight simulation tasks. In other recent studies involving ATCOs (Aricò et al, 2013, 2014, 2015b,c; Borghini et al, 2014; Di Flumeri et al, 2015; Toppi et al, 2016), it was demonstrated how it was possible to compute an EEG-based Workload Index able to significantly discriminate the workload demands of the ATM task, and to monitor them continuously by using frontal-parietal brain features. Other studies about the mental workload estimation by using neurophysiological indexes, have been proposed also in other operational contexts (Car drivers - Kohlmorgen et al, 2007; Borghini et al, 2012a; military domain - Dorneich et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…More recently, Shou et al (2012) found that “the frontal theta EEG activity was a sensitive and reliable metric to assess workload […] during an ATC task at the resolution of minute (s).” The same findings have been highlighted by Borghini et al (2013) involving pilots in flight simulation tasks. In other recent studies involving ATCOs (Aricò et al, 2013, 2014, 2015b,c; Borghini et al, 2014; Di Flumeri et al, 2015; Toppi et al, 2016), it was demonstrated how it was possible to compute an EEG-based Workload Index able to significantly discriminate the workload demands of the ATM task, and to monitor them continuously by using frontal-parietal brain features. Other studies about the mental workload estimation by using neurophysiological indexes, have been proposed also in other operational contexts (Car drivers - Kohlmorgen et al, 2007; Borghini et al, 2012a; military domain - Dorneich et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Hyperscanning permits social neuroscience to be conducted in ecologically valid contexts; Toppi et al (2016), for example, used dual-EEG to investigate inter-brain events among aircraft pilots during flight simulations, revealing patterns of between-brain coherence that differentiated between various cooperative scenarios. Hyperscanning permits social neuroscience to be conducted in ecologically valid contexts; Toppi et al (2016), for example, used dual-EEG to investigate inter-brain events among aircraft pilots during flight simulations, revealing patterns of between-brain coherence that differentiated between various cooperative scenarios.…”
Section: Discussionmentioning
confidence: 99%
“…Future research should also examine whether the interactionspecific patterns of neural coupling revealed here extend to more realworld social situations. Hyperscanning permits social neuroscience to be conducted in ecologically valid contexts; Toppi et al (2016), for example, used dual-EEG to investigate inter-brain events among aircraft pilots during flight simulations, revealing patterns of between-brain coherence that differentiated between various cooperative scenarios. It would be interesting to see whether the same patterns of neural coupling that we have observed with our interactive experimental task delineate among social exchanges with real-world implications.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, we investigated DMN by means of EEG, which has several weaknesses and limitations; it provides low resolution topography, and is only sensitive to postsynaptic potentials generated in the superficial layers of the cortex neglecting neuronal responses from structures that are deep in the brain [68]. Nevertheless, the EEG recording system has high temporal resolution and provides ecological experimental settings, whereby people are able to stay and perform psychological tasks in a more natural way [69].…”
Section: Discussionmentioning
confidence: 99%